1959
DOI: 10.1038/bjc.1959.1
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Validity of Death Certification of Cancer of the Lung in Leeds

Abstract: AN enumeration of new cases of lung cancer (i.e. cancer of the trachea, pleura, lungs or bronchi) diagnosed in 3 hospital centres in Great Britain during the years 1948-1952 was made previously (Bonser and Thomas, 1955). It was noted that more deaths were recorded than cases were diagnosed in the hospitals in two regions-Aberdeen and Leeds City. However, the figures were not strictly comparable, as not all the cases identified clinically in any year would die in the same year, though the overlap would tend to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1960
1960
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Further studies of cause of death certification relating to specific forms of morbidity have also documented extensive variability between the diagnoses contained in two or more records. Inaccuracies on the reporting of death have been noted for all of the following conditions: bacterial meningitis: Goldacre (1977); cancers: Bauer and Robbins (1972), Bosner and Thomas (1959), Dorn and Horn (1941), Hartveit (1979), Miller (1969, Murphy (1967), Rosenblatt (1971), Steer et al (1976); cerebrovascular disease: Florey (1969), KuUer (1967), Schoenberg (1968; chronic respiratory disease: Mitchel (1971); ischaemic heart disease: Rissanen (1975); liver cirrhosis: Hallen and Norden (1964). Myocardial infarction: Paton (1957); paediatric cardiovascular condition: Hook (1977); pulmonary embolism: Gorham (1961), Rossman (1974); pericarditis: Rose (1966); syphilis and alcoholism: Nicholl and Bellows (1934);tuberculosis: Edlin (1978), Khourry (1971);vascular lesions: Kagan (1967).…”
Section: Certifying Death: the Medical Cause Of Deathmentioning
confidence: 99%
“…Further studies of cause of death certification relating to specific forms of morbidity have also documented extensive variability between the diagnoses contained in two or more records. Inaccuracies on the reporting of death have been noted for all of the following conditions: bacterial meningitis: Goldacre (1977); cancers: Bauer and Robbins (1972), Bosner and Thomas (1959), Dorn and Horn (1941), Hartveit (1979), Miller (1969, Murphy (1967), Rosenblatt (1971), Steer et al (1976); cerebrovascular disease: Florey (1969), KuUer (1967), Schoenberg (1968; chronic respiratory disease: Mitchel (1971); ischaemic heart disease: Rissanen (1975); liver cirrhosis: Hallen and Norden (1964). Myocardial infarction: Paton (1957); paediatric cardiovascular condition: Hook (1977); pulmonary embolism: Gorham (1961), Rossman (1974); pericarditis: Rose (1966); syphilis and alcoholism: Nicholl and Bellows (1934);tuberculosis: Edlin (1978), Khourry (1971);vascular lesions: Kagan (1967).…”
Section: Certifying Death: the Medical Cause Of Deathmentioning
confidence: 99%
“…In a study of death certification of lung cancer in the city of Leeds, Bonser and Thomas (27) found that out of 953 cases, only 267 (28 per cent) were confirmed by autopsy. There were 210 cases (22 per cent) in which the diagnosis was based on clinical histology.…”
Section: Vol XVmentioning
confidence: 99%